(untitled) (Journal of the College of Basic Education, 2022)
The Tangier Conference /Maghreb in 1958, the most important station of unity of Morocco, through the great interest and the urgent desire of the party Maghreb parties need to hold the conference, which was held amid internal, regional and Arab conditions confirmed the value of the conference, in order to build the unity of Maghreb achieve the aspirations of the Maghreb peoples. Tangier Conference has emerged as its role and its impact significantly and effectively to Unionist Maghreb joint action, calling for reunification of the Maghreb and make diameters and one block, thus contributing to unite and objectives of the Maghreb The Conference stressed the Maghreb dimension of the Algerian revolution editorial, as conferees insisted through their sermons on the popular and official support by Tunisia and Morocco to the Algerian revolution and solidarity, stressing their support financially and morally. That most of recommendations that came out of the conference to let the issue of Maghreb unity, especially decisions about the remnants of colonial domination and its aftermath in the Maghreb region filter. French colonial power followed a divide and rule policy, so as to weaken the decisions of the Conference of Tangier, stirring strife and tension Algerian Tunisian relations through Oagele crisis on the one hand, and raised border problems between Algeria and Morocco on the other. The failure caused Conference Tangier made the disappointment appear among the peoples of the Maghreb over the loss of the desired hope to achieve the dream of Moroccans in the unit. The unity of the Arab Maghreb can be realized as not stray from the political exploitation, situational and overcome the region’s rulers national policies narrow and the need for openness of the ruling regimes in the countries of the Arab Maghreb to the new concepts of the new world order are required by the political blocs, economic and military.